2019
DOI: 10.1177/2055668319862151
|View full text |Cite
|
Sign up to set email alerts
|

NAO robot for cooperative rehabilitation training

Abstract: Introduction The aim of this research is to develop a robot-assistive training approach for the disabled individuals with impaired upper limb functions. People with impaired upper limb function can regain their motor functionality undergoing intense rehabilitation exercises. With increasing number of disabled individuals, we face deficiency in the number of expert therapists. One promising remedy could be the use of robotic assistive devices. Method To instruct and demonstrate rehabilitation exercise, this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Moreover, clinicians and patients in this study found the intervention with Pepper to be engaging, motivating, and most importantly meeting the needs of upper limb rehabilitation. Similar work has examined how the smaller, less expensive Nao robot can also deliver physical therapy for upper limb impairment, and shows similar effectiveness of this robot in rehabilitation contexts with adults [ 86 ]. Furthermore, Chen and colleagues [ 87 ] have shown that an even more compact and simple social robot (Darwin from RobotLab, San Francisco, CA, USA) can be effectively deployed to assist with children with and without cerebral palsy performing reach actions.…”
Section: Social Robots Deployed In the Wildmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, clinicians and patients in this study found the intervention with Pepper to be engaging, motivating, and most importantly meeting the needs of upper limb rehabilitation. Similar work has examined how the smaller, less expensive Nao robot can also deliver physical therapy for upper limb impairment, and shows similar effectiveness of this robot in rehabilitation contexts with adults [ 86 ]. Furthermore, Chen and colleagues [ 87 ] have shown that an even more compact and simple social robot (Darwin from RobotLab, San Francisco, CA, USA) can be effectively deployed to assist with children with and without cerebral palsy performing reach actions.…”
Section: Social Robots Deployed In the Wildmentioning
confidence: 99%
“…While it remains uncontroversial that social robots do not (yet) offer the same opportunities as humans for social interactions [33], they can nonetheless afford valuable opportunities for social engagement with human users when introduced in specific contexts, and in careful, ethically responsible ways [83,84]. A growing evidence base documents how social robots might function as autonomous tools to support psychological health interventions [42,85], physical therapy and physical health [86][87][88], and other means to amplify or support human therapeutic efforts (see [89•, 90]). Moreover, social robots are being equipped with technologies such as sensors, cameras, and processors, which promote the collection of human data (such as where a person is standing, where they are looking, what they are saying, etc.)…”
Section: Social Robots Deployed In the Wildmentioning
confidence: 99%
“…Moreover, clinicians and patients in this study found the intervention with Pepper to be engaging, motivating, and most importantlymeeting the needs of upper limb rehabilitation. Similar work has examined how the smaller, less expensive Nao robot can also deliver physical therapy for upper limb impairment, and shows similar effectiveness of this robot in rehabilitation contexts with adults[86]. Furthermore, Chen and colleagues[87] have shown that an even more compact and simple social robot (Darwin from RobotLab, San Francisco, CA, USA) can be effectively deployed to assist with children with and without cerebral palsy performing reach actions.…”
mentioning
confidence: 89%
“…offer the same opportunities as humans for social interactions [33], they can nonetheless afford valuable opportunities for social engagement with human users when introduced in specific contexts, and in careful, ethically responsible ways [83,84]. A growing evidence base documents how social robots might function as autonomous tools to support psychological health interventions [42,85], physical therapy and physical health [86,87,88], and other means to amplify or support human therapeutic efforts (see [89,90] In contrast, health interventions where more active participation is required are finding that robots with a more human-like embodiment are more effective. One such study by da Silva and colleagues [95] tested an intervention for students with the humanoid Nao robot, aimed at encouraging their motivation to exercise through motivational interviewing.…”
Section: Social Robots Deployed In the Wildmentioning
confidence: 99%
“…It has multiple degrees of freedom and sensors, as well as the integrated speech recognition support. There is a wide range of applications of NAO robot, including interventions for children with ASD [14], diabetes management [15], reduction of apathy and stabilization of cognitive performance in advanced dementia patients [16], supporting the learning of pupils with severe intellectual disabilities [17], rehabilitation training [18], reducing pediatric distress and pain in medical settings [19], and logopedic interventions [20,21]. Pepper is a humanoid robot that uses the same underlying platform.…”
Section: Robotic Technologiesmentioning
confidence: 99%